2020
DOI: 10.3390/foods9121775
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of Sociodemographic and Lifestyle Factors on Consumption of Dairy Products: Preliminary Study in Portugal and Brazil

Abstract: Sociodemographic characteristics, including regional variations, have been associated with different food consumption patterns. Behavioral factors and lifestyle variables may also contribute to different food dietary trends. In this way, the present study intended to investigate the consumption habits of the most relevant types of dairy products around the world and relate them to sociodemographic factors, for example, age, sex, education and country as well as with some anthropometric and behavioral aspects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 82 publications
2
12
0
Order By: Relevance
“…In addition, a higher income level was associated with a higher dairy product score [ 41 ]. The BMI of individuals is related to dairy product consumption [ 55 ]. However, a meta-analysis of randomized control trials and a longitudinal study demonstrated a beneficial effect of dairy intake on body weight [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a higher income level was associated with a higher dairy product score [ 41 ]. The BMI of individuals is related to dairy product consumption [ 55 ]. However, a meta-analysis of randomized control trials and a longitudinal study demonstrated a beneficial effect of dairy intake on body weight [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, few children and adolescents include dairy products in their breakfast due to socio-economic and educational factors [ 61 , 62 ]. For instance, a study in Spanish schoolchildren (9–13 years-old) found that 32% of girls and 17% of boys had a dairy product (e.g., milk, yoghurt) for breakfast [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study in Spanish schoolchildren (9–13 years-old) found that 32% of girls and 17% of boys had a dairy product (e.g., milk, yoghurt) for breakfast [ 63 ]. In general, dairy products’ consumption is low in diverse countries [ 62 ], challenging the dietary calcium recommendations associated with a diet deficient in several nutrients [ 64 ]. Finally, calcium consumption has been related to fat oxidation in adults [ 57 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Butter is a water-in-oil (W/O) emulsion. It is probably one of the oldest milk products, produced by the concentration of milk fat following the destabilisation of oil-in-water (O/W) milk or cream emulsion [2]. The butter is obtained by processing milk.…”
Section: Introductionmentioning
confidence: 99%